Artificial Intelligence and the Future of Education: The impact of ChatGPT on Students’ academic achievement - Shwana Akoi; Ferman Ismael; Tina Naseri (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
In this research, we analyze how ChatGPT, an artificial intelligence-based tool, might affect academic outcomes. The chosen title succinctly conveys the central focus of the article, providing a clear and comprehensive overview of the exploration into how ChatGPT, as a representation of artificial intelligence, is influencing students' academic achievement within the context of the evolving educational landscape. The study applied quantitative research method. Incorporating AI-based solutions like ChatGPT has been shown to improve individualized education, according to the study's findings. Ethical issues, including data privacy and bias, are also highlighted as crucial when employing AI-based tools in the classroom. The results demonstrated that artificial intelligence-based tools like ChatGPT could significantly improve teaching and learning. Moreover, it is crucial to make sure that ethical considerations direct the integration and that instructors and educators are given the proper training to use the tools successfully to encourage individualized learning.